PEMIKIRAN ABDUL MALIK FADJAR DAN K.H. ABDUL WAHID HASYIM TENTANG PENDIDIKAN ISLAM - Ahmad Budiyono; Hani Adi Wijono; Ramli Ramli (STAI Darussalam Lampung, 2023)
The thought of Abdul Malik Fadjar and the thought of K.H Abdul Wahid Hasyim in general shows the thought of Islamic education that must show fundamental changes and improvements in the system and management of Islamic education to achieve quality educational goals that can mobilize all educational resources, which are taken from the thought of Abdul Mallik Fadjar and the thought of KH. Abdul Wahid Hasyim.The type of research is litrer or library research. Based on the results of the study that, The values contained in Islamic education according to Abdul Malik Fadjar are to form students to develop as a generation of khaih ummah, faith and devotion, mature in attitude, have independent thinking and spirit, creative, dynamic and noble character, and K.H Abdul Wahid Hasyim is a bridge to change, with education stupid people can be smart by learning.